Recombinant Neorudin for the Prevention of Deep-Vein Thrombosis After Spinal-Cord Injury - Liu YB; Liu Y; Zhang L; Zhou XC; Ren BY; Zheng C; Hao CH; Wang WT; Xia X; Zhou GQ; Wu CT; Jin JD (Dove Medical Press, 2023)
Yu-Bin Liu,1,2 Yun Liu,1,3 Lin Zhang,1 Xing-Chen Zhou,1 Bo-Yuan Ren,1 Can Zheng,1 Chun-Hua Hao,4 Wei-Ting Wang,4 Xia Xia,5 Gang-Qiao Zhou,1,3 Chu-Tse Wu,1 Ji-De Jin1 1Department of Experimental Hematology and Biochemistry, Beijing Institute of Radiation Medicine, Beijing, People's Republic of China; 2Division of (Bio) Pharmaceutics, Institute of Zhejiang University - Quzhou, Zhejiang, People's Republic of China; 3School of Medicine, Guizhou University, Guiyang, People's Republic of China; 4Center for Pharmacodynamic Research, Tianjin Institute of Pharmaceutical Research, Tianjin, People's Republic of China; 5Beijing SH Biotechnology Co., Ltd., Beijing, People's Republic of ChinaCorrespondence: Chu-Tse Wu; Ji-de Jin, Email wuct@bmi.ac.cn; jinjide505@163.comBackground: Whether anticoagulant therapy should be used after spinal-cord injury (SCI) surgery was controversial. The anticoagulation characteristics of a newly developed anticoagulant, recombinant neorudin (EPR-hirudin (EH)), were explored using a rat model of SCI to provide a basis for clinical anticoagulation therapy of SCI.Methods: A rat model of SCI was developed by Allen's method. Then, thrombosis in the inferior vena cava was induced by ligation. The low-bleeding characteristics of EH were explored by investigating dose-response and time-effect relationships, as well as multiple administration of EH, on thrombus formation complicated with SCI.Results: EH inhibited thrombosis in a dose-dependent manner by reducing the wet weight and dry weight of the thrombus. An inhibiting action of EH on thrombosis was most evident in the group given EH 2 h after SCI. After multiple intravenous doses of EH, thrombosis inhibition was improved to that observed with low molecular weight heparin (LMWH) (87% vs 90%). EH administration after SCI neither increased bleeding in the injured spine nor damaged to nerve function. Bleeding duration and activated partial thromboplastin time were increased in the high-dose EH group compared with that in the normal-saline group, but were lower than those in the LMWH group.Conclusion: EH can reduce thrombus formation in a rat model of SCI, and bleeding is decreased significantly compared with that using LMWH. EH may prevent thrombosis after SCI or spinal surgery.Keywords: recombinant neorudin, rat model, thrombosis, spinal-cord injury, low-bleeding anticoagulation